2021
DOI: 10.1007/s00330-020-07635-6
|View full text |Cite|
|
Sign up to set email alerts
|

Radiomics score predicts acute respiratory distress syndrome based on the initial CT scan after trauma

Abstract: Objectives Acute respiratory distress syndrome (ARDS) constitutes a major factor determining the clinical outcome in polytraumatized patients. Early prediction of ARDS is crucial for timely supportive therapy to reduce morbidity and mortality. The objective of this study was to develop and test a machine learning–based method for the early prediction of ARDS derived from the first computed tomography scan of polytraumatized patients after admission to the hospital. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Commercial CT-based tools are available for triage or detection and grading of intracranial hemorrhage and spine fractures. Proof-of-concept tools in earlier stages of the R&D pipeline include those for detection of active hemorrhage and aortic injury; detection and grading of pelvic fractures; detection, quanti cation, and grading of solid organ lacerations; as well as detection and quanti cation of traumatic extraperitoneal pelvic hematoma, hemoperitoneum, hemothorax, and pulmonary contusion [22,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial CT-based tools are available for triage or detection and grading of intracranial hemorrhage and spine fractures. Proof-of-concept tools in earlier stages of the R&D pipeline include those for detection of active hemorrhage and aortic injury; detection and grading of pelvic fractures; detection, quanti cation, and grading of solid organ lacerations; as well as detection and quanti cation of traumatic extraperitoneal pelvic hematoma, hemoperitoneum, hemothorax, and pulmonary contusion [22,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to COVID-19 pneumonia, blunt chest trauma is also currently associated with parenchymal lung injury to various extents, which may increase the risk of developing ARDS. Typically, the presence of an injury severity score (ISS) greater than 25 significantly increases the risk of developing ARDS [18]. Moreover, it has previously been shown that trauma patients with pulmonary contusions involving at least 20% of the total lung volume have a significantly higher risk of developing ARDS [40].…”
Section: Prediction Of Ardsmentioning
confidence: 99%
“…Blunt chest trauma is currently associated with parenchymal lung injury at various extents, which may increase the risk of developing ARDS. Usually, the presence of an injury severity score (ISI) higher than 25 significantly increases the risk of developing ARDS [8]. In addition, it has previously been shown that trauma patients with pulmonary contusions involving at least 20% of the total lung volume had a significantly higher risk of developing ARDS [9].…”
Section: Prediction Of Ardsmentioning
confidence: 99%
“…One hundred twenty-three patients were enrolled. The model consisted in a fully automated ML and radiomics based approach, that had a higher accuracy compared to an established score (ISS and abbreviated injury score of the thorax) to identify ARDS in trauma patients [8]. In this line, a rapid automated chest CT volumetry assessment of pulmonary contusion in trauma patients showed a good accuracy to assess the risk of ARDS, length of intensive care and time on mechanical ventilation [10].…”
Section: Prediction Of Ardsmentioning
confidence: 99%